Electrospun Polyvinyl Alcohol Nanofibers Containing Titanium Dioxide for Gas Sensor Applications - El Fawal, Gomaa F.; Hassan, H. Shokry; El-Aassar, Mohamed R.; Elkady, Marwa F. (Arabian journal for science and engineering (2011), 2019)
Electrospun nanofibers for gas sensor application were effectively prepared from polyvinyl alcohol and pluronic solution with different percentages of titanium dioxide ( TiO 2 ) nanoparticles. Nanofibers membrane was subject to detailed analysis by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and thermal gravimetric analysis (TGA). Adding TiO 2 nanoparticles to the blended solution increased nanofibers diameters from 280 ± 20 to 310 ± 30 nm . The gas sensor response of TiO 2 nanofibers (as a function of temperature) was estimated toward liquid petroleum gas (LPG), CO 2 , and O 2 and compared with pure nanofibers. The maximum response value (100%) was obtained for LPG at 160 ∘ C with TiO 2 nanofibers (0.01%). These results show promising gas sensing characteristics (such as lower operating temperatures and sufficient gas responses) for those nanofibers materials.